2017
DOI: 10.1073/pnas.1615922114
|View full text |Cite
|
Sign up to set email alerts
|

Determining climate effects on US total agricultural productivity

Abstract: The sensitivity of agricultural productivity to climate has not been sufficiently quantified. The total factor productivity (TFP) of the US agricultural economy has grown continuously for over half a century, with most of the growth typically attributed to technical change. Many studies have examined the effects of local climate on partial productivity measures such as crop yields and economic returns, but these measures cannot account for national-level impacts. Quantifying the relationships between TFP and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
114
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(138 citation statements)
references
References 40 publications
8
114
1
2
Order By: Relevance
“…While the rate of increase in crop yields in much of the world has been more modest than observed for the USA (Ray et al 2013), the introduction of hybrids and improved genetics and agronomic practices has driven a >3-fold increase in maize yields over the past 60 yr in the USA, from~53 bushels per acre (3328 kg/ha) in the 1956 to~170 bushels per acre (10,676 kg/ha) in 2016 (USDA NASS 2017; Appendix S1). A number of changes in the climate system will, however, conspire to work against extrapolating these historic increases in grain yields into the future (Lobell and Field 2007, Zipper et al 2016, Liang et al 2017, Angel et al 2018. Indeed, contemporary record maize yields in the United States are more than twice this value (Agfax 2016, https:// agfax.com/2016/12/20/georgia-farmer-at-top-of-500-bushel-national-corn-yield-contest-dtn/), and predictions based on the theoretical limits to net primary production would be higher still (DeLucia et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While the rate of increase in crop yields in much of the world has been more modest than observed for the USA (Ray et al 2013), the introduction of hybrids and improved genetics and agronomic practices has driven a >3-fold increase in maize yields over the past 60 yr in the USA, from~53 bushels per acre (3328 kg/ha) in the 1956 to~170 bushels per acre (10,676 kg/ha) in 2016 (USDA NASS 2017; Appendix S1). A number of changes in the climate system will, however, conspire to work against extrapolating these historic increases in grain yields into the future (Lobell and Field 2007, Zipper et al 2016, Liang et al 2017, Angel et al 2018. Indeed, contemporary record maize yields in the United States are more than twice this value (Agfax 2016, https:// agfax.com/2016/12/20/georgia-farmer-at-top-of-500-bushel-national-corn-yield-contest-dtn/), and predictions based on the theoretical limits to net primary production would be higher still (DeLucia et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Field-trials of U.S. wheat varieties have revealed that newer seed varieties exhibit less resistance to yield reduction from extreme spring-time temperatures (Tack, Barkley, & Nalley, 2014, 2015. Liang et al (2017) inferred that the negative climate effects would outweigh the net technological gains in U.S. agriculture to decrease its total factor productivity (TFP) to 1980 levels before the year 2050. Ortiz-Bobea, Knippenberg, and Chambers (2018) found that the agricultural TFP of the Midwestern U.S. region has become more sensitive to hotter temperatures since the 1980s.…”
mentioning
confidence: 99%
“…Shifts in climatic conditions in the Midwest, such as changes in extreme precipitation events at important stages in crop development, pose risks of significant damages to crop productivity and environmental sustainability . On an annual basis, extreme rain events can delay planting or cause waterlogging that reduces the efficiency or TFP of agriculture . Extreme rains are also implicated in degradation of soil resources through erosion, which reduces the long‐term productive capacity of agricultural lands .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Extreme precipitation is defined as an event with more than 4 inches (101.6 mm) of rain in a 24‐hour period . Such events can reduce the efficiency or total factor productivity (TFP) of agriculture . For example, in the early growing season, extreme precipitation events can delay planting and increase farmers’ economic risks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation